System of planning and evaluation of school meals. Issue 6 (7th August 2013) - Rocha, Ada; Afonso, Cláudia; Santos, M Cristina; Morais, Cecília; Franchini, Bela; Chilro, Rui
Abstract: Objective: To develop a software to plan and evaluate school meals according to the main national and international standards for foods and nutrition. Design: Development of software. Setting: Public schools, Portugal. Subjects: School meals for students. Results: The System of Planning and Evaluation of School Meals (SPARE) is a software that allows the planning of school meals in an effective and organized way, according to the main national and international standards for food and nutrition. The regular use of this tool enables the evaluation, monitoring and verification towards continuous improvement of the quality of school meals. Conclusions: The SPARE software aims to promote healthy eating by focusing on the planning and production of safe and adequate meals in the school environment. This software can be adapted to different age groups and to different contexts, attending to specific nutritional and food standards.